AWS Certified Database – Specialty (DBS-C01) Cert Prep: 3 Migration and Management. - Carpenter, Tom (linkedin.com, 2020)
Review database migration strategies and the basic processes used in database management as you prepare for the AWS Certified Database – Specialty (DBS-C01) exam.